Intestinal Lymphangiectasia in a Maltese dog: Case report (Research, Society and Development, 2025)
Intestinal lymphangiectasia is a chronic condition characterized by dilation of the intestinal lymphatic vessels, leading to loss of proteins into the intestinal lumen. The condition can cause chronic diarrhea, weight loss, ascites, and hypoalbuminemia, and is more common in small breeds, such as Maltese and Yorkshire Terrier. This study aims to report a clinical case of a 10-year-old male Maltese dog with foul-smelling diarrhea, apathy, progressive weight loss, alopecia, and cavitary effusions. Laboratory tests revealed anemia, lymphopenia, and severe hypoalbuminemia. Abdominal ultrasonography indicated jejunal enteropathy associated with ascites, and the definitive diagnosis was obtained by histopathological analysis of a sample collected by endoscopy, which confirmed lymphangiectasia associated with lymphoplasmacytic duodenitis. Treatment included a lipid-lowering diet, corticosteroids, fat-soluble vitamin supplementation, and plasma infusion in episodes of critical hypoalbuminemia. The patient was also monitored by a veterinary nutritionist and gastroenterologist and was hospitalized for clinical stabilization. Despite periods of clinical improvement with the therapy instituted, the dog did not resist the progression of the disease and died after five months of follow-up. This study highlights the importance of early diagnosis and appropriate therapeutic approach in cases of intestinal lymphangiectasia, considering the severity and poor prognosis of the disease.